2020
DOI: 10.1186/s12883-020-01800-6
|View full text |Cite
|
Sign up to set email alerts
|

Palato-pharyngo-laryngeal myoclonus with recurrent retrograde feeding tube migration after cerebellar hemorrhagic stroke: a case report and review of hypertrophic olivary degeneration

Abstract: Background: Palato-pharyngo-laryngeal myoclonus, a variant of palatal myoclonus, is characterized by involuntary rhythmic movements of palatal, pharyngeal, and laryngeal muscles. Symptomatic palatal myoclonus is classically associated with hypertrophic olivary degeneration on MRI imaging due to a lesion in the triangle of Guillain-Mollaret. Case presentation: We report a case of palato-pharyngo-laryngeal myoclonus in a patient post-cerebellar hemorrhagic stroke who presented with recurrent retrograde migration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
(34 reference statements)
0
5
0
1
Order By: Relevance
“…It is reported that symptomatic palato-pharyngo-laryngeal rhythmic myoclonus in NBS presents anywhere between 1 month and 8 years after the initial lesion. 8…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that symptomatic palato-pharyngo-laryngeal rhythmic myoclonus in NBS presents anywhere between 1 month and 8 years after the initial lesion. 8…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that symptomatic palato-pharyngolaryngeal rhythmic myoclonus in NBS presents anywhere between 1 month and 8 years after the initial lesion. 8 Palato-pharyngo-laryngeal rhythmic myoclonus is a unique otolaryngologic presentation of Neuro-Behcet's disease with several laryngeal complications. First, the synchronous myoclonus of the vocal folds, in combination with presumed multifocal CNS lesions, resulted in significant dysarthria with dysphonia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Palatal myoclonus can rarely be associated with synchronous myoclonus of other branchial arch muscles, the diaphragm, facial muscles, or even the extremities 2 . One specific variant is termed palato‐pharyngo‐laryngeal myoclonus, which can result in dysphagia, dysphonia, and dysarthria 4 …”
Section: Figmentioning
confidence: 99%
“…2 One specific variant is termed palato-pharyngo-laryngeal myoclonus, which can result in dysphagia, dysphonia, and dysarthria. 4 A 56-year-old woman awoke from sleep with new right-sided weakness and dizziness. Magnetic resonance imaging (MRI) of the brain showed restricted diffusion in the right superomedial cerebellum consistent with an acute infarct (Fig.…”
mentioning
confidence: 99%